Genetic Diversity of Type 3 Secretion System in Burkholderia s.l. and Links With Plant Host Adaptation - Wallner, Adrian; Moulin, Lionel; Busset, Nicolas; Rimbault, Isabelle; Béna, Gilles (Frontiers in Microbiology, 2021)
Burkholderia sensu lato species are prominent for their diversity of hosts. The type III secretion system (T3SS) is a major mechanism impacting the interactions between bacteria and eukaryotic hosts. Besides the human pathogenic species Burkholderia pseudomallei and closely affiliated species, the T3SS has received little attention in this genus as in taxonomically and evolutionary close genera Paraburkholderia, Caballeronia, Trinickia and Mycetohabitans. We proceeded to identify and characterize the diversity of T3SS types using the genomic data from a subset of 145 strains representative of the species diversity found in the Burkholderia s.l. group. Through a phylogenetic distribution, we identified two new T3SS types with an atypical chromosomal organization and which we propose to name BCI (Burkholderia cepacia complex Injectisome) and PSI (Paraburkholderia Short Injectisome). BCI is the dominant T3SS type found in Burkholderia sensu stricto (s.s.) species and PSI is mostly restricted to the Paraburkholderia genus. By correlating their distribution with the ecology of their strains of origin, we propose a role in plant interaction for these T3SS types. Experimentally, we demonstrated that a BCI deficient B. vietnamiensis LMG10929 mutant was strongly affected in its rice colonization capacity.